2017
DOI: 10.3389/fpsyg.2017.01500
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Discrepancy on Children’s Body Weight Perception: The Role of Attachment Security

Abstract: The discrepancies between parents and their children on the description of the behavior and representations of their children have been shown in various studies. Other researchers have reported the parents’ difficulty in correctly identifying the weight status of their children. The purpose of our study was to investigate the parent’s attributional accuracy on their children’s body weight perception in relation to the children attachment security. It was hypothesized that insecure children’s parents have a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…On the other hand, the lack of attachment and security caused by neglect exacerbates the parent-child discrepancy in children's BWP. A study by Uccula et al indicated that parents of children with insecurities had a tendency to underestimate the actual body weight of their children, particularly those who were overweight or obese ( 32 ). In this situation, parents believe that their children perceive themselves as more obese than the parents perceive them, and unconsciously construct an obesogenic family environment ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the lack of attachment and security caused by neglect exacerbates the parent-child discrepancy in children's BWP. A study by Uccula et al indicated that parents of children with insecurities had a tendency to underestimate the actual body weight of their children, particularly those who were overweight or obese ( 32 ). In this situation, parents believe that their children perceive themselves as more obese than the parents perceive them, and unconsciously construct an obesogenic family environment ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…We are not familiar with any previous research that includes a stranger’s assessment of the respondent’s weight. Studies exist that analyze weight assessments by others, but these studies use selective samples (Christensen, 2012; Doolen et al, 2009; Pulvers et al, 2008; Tovee et al, 2000; Vella-Zarb and Mills, 2011) and only a few include measures of both the respondent’s and the observer’s assessment of the respondent’s weight (Goodman et al, 2000; Pulvers et al, 2008; Uccula and Nuvoli, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…According to attachment theory, family messages have the capacity to create environments of either safety and security or rejection and abandonment, depending on the nature of the message, and these messages can have implications for psychosocial health (Holmes & Farnfield, 2022). Preliminary literature shows this to be particularly true when messages center beliefs about weight, body image, and food (Kerbs & El‐Alayli, 2016; Uccula & Nuvoli, 2017; Yourell et al, 2021). Weight talk within the family occurs in multiple different forms, including family weight teasing (FWT) and parental encouragement to diet.…”
Section: Introductionmentioning
confidence: 99%